Rekomendasi Pemenuhan Gizi Ibu Hamil dengan Kekurangan Energi Kronik dan Penyuluhan Pemberian Asi Eksklusif Jember - Sri Kurniawati, Rita; Rakhmawati, Dewi; Anam, Khoirul (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
One of the problems contributing to 40% of maternal deaths in developing countries is Chronic Energy Deficiency (CED). Mothers who are at risk of CED will cause several problems for both the mother and fetus. The result of Riskesdas (2018) shows that the prevalence of CED in Indonesia is 17.3%, apart from nutritional problems and nutritional disorders that often occur in pregnant women, nutritional fulfillment for babies is crucial. According to the Ministry of Health in 2019, 65% of babies did not receive exclusive breast milk during the first 6 months of birth. This number is still far from the target of exclusive breastfeeding coverage in 2019 set by WHO and the Ministry of Health, namely 50%. This community service was carried out in March 2024 in Rambigundam Village, Rambipuji, Jember. This service was carried out because there were 3 pregnant women with CED and the low fulfilling rates for exclusive breastfeeding for babies in Rambigundam Village. The methods used in this community service are providing counseling and providing additional food to pregnant women and mothers with babies, as well as conducting evaluations. The evaluation results showed that there was an increase in body weight in the three pregnant women with Chronic Energy Deficiency and the evaluation of exclusive breastfeeding monitoring showed that the frequency of breastfeeding increased and the usages of formula milks were decreased.